Generating Variable Bessel Beam Profiles With a Transmission Grating - De Ubago, Adrian Matthew U (Archīum Ateneo, 2020)
We present a simple mechanism for varying the core diameter of zero-order Bessel beams (BBs) through the use of a commercially available diffraction grating. A standard set-up to generate BBs is employed, based on an annular slit and a lens. Output BBs are made to pass through transmission gratings with different groove densities. Core diameters and propagation behavior are modified for BBs diffracted by gratings at diffraction orders m = 0 and m = 1.